ASSESMENT AND WRITING (Ustozlar uchun, 2025)
Assessment and testing are essential components of the educational process that aim to evaluate students’ learning, skills, and competencies. Assessment refers to the systematic collection of information about a learner’s performance to improve teaching and learning, while testing is a tool within assessment that measures specific knowledge or abilities through standardized procedures. Various types of assessment exist, including formative, summative, diagnostic, and criterion-referenced assessments. Effective assessment and testing strategies help educators identify strengths and weaknesses, guide instructional decisions, and enhance student achievement. Additionally, they play a crucial role in maintaining educational standards and accountability.